THE USE OF TPR METHOD FOR DISABLE STUDENTS WITH DIFFERENT LEARNING STYLES IN ENGLISH VOCABULARY DEVELOPMENT - Zul Astri; Isnaeni Wahab (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2019)
Teaching English as a foreign language to mentally retarded persons is much more complicated than normal EFL students, and it requires specific techniques and methods. The aims of the research are to find out the profile of disabled students’ learning style and to elaborate on how well Total Physical response meets the needs of disabled students with different learning styles. This research applied pre-experimental design which used to see the result of applying the TPR Method for disable students with different learning styles in vocabulary development and the data were obtained from the questionnaire, interview, and classroom observation. The research result shows that there are 3 types of learning styles in the classroom, namely visual learning, auditory and kinesthetic learning style. The data revealed that the average pre-test results of students before being given teaching material using the TPR method is 5% while the results obtained by students after giving teaching material using the TPR method is 77%. 100% of visual learners have improved the result of the post-test after being given the material. 100% of auditory learners also have an increase in the result of the post-test after the provision of teaching materials using the TPR method. However, only 50 percent of 100 percent kinesthetic learners experience an increase after the provision of teaching materials using the TPR method. There are many factors that can influence the result of the student’s test. It can be in the form of internal factors that can stimulate the concentration and the motivation of students in learning English